Nivolumab and Stereotactic Radiosurgery for Patients With Breast Cancer Brain Metastases: A Nonrandomized, Open-Label Phase 1b Study - Kamran A. Ahmed, MD; Youngchul Kim, PhD; John A. Arrington, MD; Sungjune Kim, MD, PhD; Michelle DeJesus, BS; Aixa E. Soyano, MD; Avan J. Armaghani, MD; Ricardo L.B. Costa, MD; Hung T. Khong, MD; Loretta S. Loftus, MD; Marilin Rosa, MD; Jimmy J. Caudell, MD, PhD; et al. (Advances in Radiation Oncology, 2021)
Purpose: We hypothesize treatment with nivolumab and stereotactic radiosurgery (SRS) will be feasible and well tolerated, and may improve intracranial tumor control rates compared with SRS alone. Methods and Materials: The study was designed as a prospective, single-arm, nonrandomized, open-label, phase 1b trial of nivolumab and SRS among patients with metastatic breast cancer brain metastases. Key eligibility criteria included patients with breast cancer brain metastases of all subtypes, age ≥18, Eastern Cooperative Oncology Group Performance Status ≤2 with ≤10 brain metastases. Treatment was initiated with a dose of nivolumab (480 mg intravenously) that was repeated every 4 weeks. The initial dose of nivolumab was followed 1 week later by SRS. This study is closed to accrual and is registered with ClinicalTrials.gov, NCT03807765. Results: Between February 2019 and July 2020, a total of 12 patients were treated to 17 lesions. No dose limiting toxicities were noted in our patient population. The most common neurologic adverse events included grade 1 to 2 headaches and dizziness occurring in 5 (42%) of patients. Median intracranial control was 6.2 months (95% confidence interval, 3-14 months) with 6- and 12-month control rates of 55% and 22%, respectively. A total of 4 patients had systemic progression during the study. Median time to systemic progression free survival has not been reached with 6- and-12 month rates of 63% and 51%, respectively. Conclusions: Nivolumab and SRS is a safe and feasible treatment option in breast cancer brain metastases. Preliminary data reveals activity in certain breast cancer patients to study therapy.